Comparison of Intranasal Ciclesonide, Oral Levocetirizine, and Combination Treatment in Patients with Allergic Rhinitis. (2nd September 2014) - Kim, Chang‐Hoon; Kim, Jin Kook; Kim, Hyun Jun; Cho, Jin Hee; Kim, Young‐Dae; Lee, Heung‐Man; Yoon, Joo‐heon
Abstract : Objectives: Ciclesonide is an intranasal corticosteroid for the treatment of allergic rhinitis. To date, concrete evidence to justify a definitive recommendation of intranasal corticosteroid over oral antihistamine has not been demonstrated. This study aimed to evaluate the efficacy and safety of once‐daily ciclesonide in comparison to both levocetirizine alone, and a ciclesonide/levocetirizine combination in patients with seasonal (SAR) and perennial AR (PAR). Methods: Subjects exhibiting moderate to severe allergic rhinitis for longer than 1 year were randomized in an open‐label, 3‐arm, parallel group, multicenter study. Subjects received 200 µg ciclesonide, 5 mg levocetirizine, or a combination of both. Changes from baseline until the end‐of‐study visit (2 weeks following) were evaluated by reflective total nasal symptom scores (rTNSS), reflective total ocular symptom scores (rTOSS), physician‐assessed overall nasal signs and symptoms severity (PANS), and rhinoconjunctivitis quality‐of‐life questionnaires (RQLQ). Results: Significant improvements in rTNSS, PANS, and RQLQ in the ciclesonide monotherapy group were observed in comparison to the levocetirizine alone group. Three individual symptoms of rTNSS were improved in the ciclesonide‐treated group. rTOSS scores for ciclesonide monotherapy improved from baseline, but no superiority over levocetirizine was shown. Ciclesonide spray was more effective than levocetirizine in reducing nasal symptoms in both SAR and PAR patients. Ciclesonide and levocetrizine were well tolerated alone and in combination. Conclusions: Our results provide support for an AR and its Impact on Asthma (ARIA) recommendation stipulating that ciclesonide is superior to levocetirizine for the treatment of AR, with tolerable safety. Addition of levocetirizine to ciclesonide did not give further clinical benefit over monotherapy.